Pengembangan Aplikasi Mobile Travel Guide di Provinsi Lampung - Della Niken Indriani; Muhammad Said Hasibuan; Triowali Rosandy (Journal of Digital Literacy and Volunteering, 2026)
Lampung Province has significant tourism potential, supported by a wide variety of natural, cultural, and culinary attractions. However, tourism information is still scattered across various platforms and lacks integration, making it difficult for tourists to access accurate and reliable information. This study aims to develop a mobile travel guide application as an integrated tourism information center for Lampung Province that is structured, interactive, and easily accessible. The research method used is Research and Development (R&D) with the Waterfall system development model, which consists of requirement analysis, system design, implementation, testing, and maintenance stages. The application is developed using Progressive Web App (PWA) technology, enabling mobile access, offline functionality, and responsive performance. The main features of the application include tourism destination information, interactive maps, travel routes, accommodation, culinary recommendations, souvenir centers, and local events. System testing is conducted using black-box testing to ensure that all functionalities operate as expected. In addition, user experience evaluation is carried out using the User Experience Questionnaire (UEQ). The results indicate that the developed application successfully provides integrated tourism information and achieves a good level of user satisfaction. Therefore, this application is expected to assist tourists in planning their trips more effectively and to support digital tourism promotion in Lampung Province.